Manajemen Cairan pada Pasien Hemodialisis Untuk Meningkatkan Kualitas Hidup di RSUD Dr. Harjono Ponorogo - Isroin, Laili (IJNP (Indonesian Journal of Nursing Practices), 2015)
Patients with chronic renal failure require renal replacement therapy for life. One of renal replacement therapy is hemodyalisis. Patient who is experiencing hemodialisa will experience degradation of quality of life. Haemodialysis patients’s quality of life are fl uctuating because their health is infl uenced by physical, psychological, level of independence, social relationships, personal beliefs and their relationship with the environment. Fluid management assists patient on adapating the change of their health status and improve their quality of life.The aim of this study was to determine the eff ect of fl uid management therapy to the quality of life on hemodialysis patient. This study used an experimental research design with pre-test post-test approach to controls. Samples were divided into 2 groups: an intervention group of 6 people and a control group of 5 people were randomly assigned. The data was taken on 2 periods: the fi rst was before interventions were given, and the second was after 12-16 times of haemodyalisis after the interventions were given. The results showed that the quality of life of patients treated group was higher (53.82) than the control group (39.33). There were no differences in changes in quality of life based on the KDQOL SF-36 questionnaire, between treatment groups with the control group.Keywords: Chronic renal failure, hemodyalsis, fluid management, quality of life